A POPULAR CULTURE RESEARCH ON AMERICAN HEGEMONY IN TRANSNATIONAL WOMEN MAGAZINE ADVERTISEMENTS - Ekawati Marhaenny Dukut (Rubikon : Journal of Transnational American Studies, 2015)
Women magazine advertisements from the United States of America (U.S.A.) cross border in space of time and location due to the transnational characteristics of American popular culture. By traveling through spaces of time, an advertisement from previous years is possible to come up again in many years after. This occurence happens in some U.S. women magazine advertisements. Meanwhile through spaces of location, U.S. magazine advertisements can also be published in magazines from other nations with almost no real difference in its visualizations, like what happens in Indonesian women magazines. Scholars claim the occurrence is influenced by the American hegemony phenomena. Working under the American Studies discipline, the researcher chooses a total of 3621 women magazine advertisements from the 2007-2008 issues of U.S. Ladies Home Journal, O: The Oprah Magazine, Cosmopolitan; Indonesian Cosmopolitan, Kartini, and Femina, as well as 1960 Ladies Home Journal to become the main data for research. In her research, a thread of popular culture, consumer culture and gender ideology perspectives are found. First, through popular culture, the advertisements gain an easy access for transnationality and globalization. Second, through consumer culture, the researcher finds that women are acknowledged as the highest potential as consumers because they are the decision makers of their own family’s household expenses. Third, by dissecting and analyzing the advertisements in more detail, the research also finds that gender ideology confirms how society still want women to maintain the traditional roles of women as mothers and housewives.Keywords: Transnational American Studies, popular culture, hegemony, gender ideology